2020
DOI: 10.2147/cmar.s275038
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acceptance of Human Papillomavirus Vaccination and Associated Factors Among Parents of Daughters in Gondar Town, Northwest Ethiopia</p>

Abstract: Background: Cervical cancer is one of the profound threats to women's lives and the fourth most common cancer among women. Ethiopia launched the human papilloma vaccination for the first time, with the support of the Global Alliance for Vaccine and Immunization (GAVI) in 2018. Therefore, the aim of this study was to assess the acceptability of the human papillomavirus vaccine and associated factors among parents of daughters in Gondar town, Northwest Ethiopia. Methods: A community-based cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 24 publications
10
49
1
Order By: Relevance
“…19,20 When we compare the acceptance rate of the COVID-19 vaccine of the Ethiopian population with other vaccination programs in Ethiopia it indicates a huge difference. For instance, the study conducted to assess the acceptance of human papilloma vaccine (HPV) showed that the majority of the respondents (81.3% 21 and 81.8% 22 ) accepted that the HPV could be administered to their teenage girls. Some studies also indicated that only a small fraction of the population are vaccine non-receipt and refusal in Ethiopia towards the expanded program on immunization coverage survey.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 When we compare the acceptance rate of the COVID-19 vaccine of the Ethiopian population with other vaccination programs in Ethiopia it indicates a huge difference. For instance, the study conducted to assess the acceptance of human papilloma vaccine (HPV) showed that the majority of the respondents (81.3% 21 and 81.8% 22 ) accepted that the HPV could be administered to their teenage girls. Some studies also indicated that only a small fraction of the population are vaccine non-receipt and refusal in Ethiopia towards the expanded program on immunization coverage survey.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using a questionnaire which was adapted after a thorough literature review of previously conducted studies [ 10 , 14 , 20 , 21 ]. The questionnaire was translated to Amharic to avoid language barrier.…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable of the study was acceptability of HPV vaccination which was assesses by using a question “Are you willing to vaccinate your daughter for HPV vaccination which can protect against HPV infection? [ 10 , 22 ]. The independent variables assessed in the study includes monthly income, marital status, educational status of the parents, knowledge on cervical cancer, knowledge of HPV, knowledge of vaccine, and attitude towards the vaccine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations